'I Want There to be no Glass Ceiling:' Evangelicals' Engagements with Class, Education, and Urban Childhoods. (February 2017) - Strhan, Anna
While class has been an enduring focus for sociologists of education, there has been little focus on the interrelations between class, religion, and education, despite widespread public anxieties about faith schools potentially encouraging both social class segregation and religious separatism, which have become more pronounced as the expansion of free schools and academies in England has increased opportunities for religious bodies' engagement in educational provision. This article explores the importance of class in relation to the intersections of religion and education through examining how an 'open evangelical' church engages with children in schools linked with it, drawing on eighteen months' ethnographic fieldwork with the church, its linked schools, and other informal educational activities run by the church. Through analyzing the everyday practices through which evangelical leaders seek to affect children's lives and how they speak about their involvements with children, the article reveals the significance of class in this context, providing insight into how evangelicals' primary aspiration in this setting is for children's 'upward mobility', as their ambitions are shaped through middle-class, entrepreneurial norms, in which developing a neoliberal ethic of individual self-discipline and 'productivity' is privileged. Through focusing on the 'othering' of the urban poor in these discourses, the article adds to our knowledge of the complex interrelations between evangelicalism and class, and deepens understanding of how secular neoliberal norms become interwoven with an alternative evangelical moral project of forming the self.